Analysis of Community Participation in the Development of Dolli Tourism Village, Tukamasea Village, Bantimurung District, Maros Regency - Rahmaniar, Rahmaniar; Edison, Edison (Asosiasi Ide Bahasa Kepri, 2024)
Community involvement in the development of the Dolli Tukamasea Tourism Village, located in Tukamasea Village, Bantimurung District, Maros Regency, is a crucial component in efforts to achieve sustainable development. This study aims to assess the extent of community participation in the development of the Dolli Tukamasea Tourism Village. A descriptive qualitative method is employed, utilizing both primary and secondary data sources. Data collection techniques include interviews, observation, and documentation. The theoretical framework is based on Josef Riwu Kaho's (2007:127) model of community participation, which encompasses four types of participation: (1) Participation in decision-making, (2) Participation in implementation, (3) Participation in evaluation, and (4) Participation in benefit-sharing. The findings of the study indicate that community participation in the development of the Dolli Tukamasea Tourism Village is highly effective. Firstly, participation in decision-making is conducted through deliberative processes where community members share their opinions and input on program decisions related to the village's development. Secondly, participation in implementation involves the active engagement of all community members in the development efforts. Thirdly, participation in evaluation is evident as the community collectively strives to innovate and assume responsibility for the village's progress. Lastly, participation in benefit-sharing is realized as the economic benefits of the tourism village are felt by the local community, contributing positively to their livelihoods.